Transcutaneous oxygen pressure and hemorheology in diabetes mellitus - Le Devehat, C; Khodabandehlou, T (International angiology, 1990)
Diabetes is associated with altered blood viscosity and abnormal tissue oxygenation. Transcutaneous oxygen tension is measured in 119 diabetic and 20 normal subjects. Measurements of transcutaneous oxygen pressure (TcPO2) are made by Oxymonitor SM 361 at 45 degrees C at the dorsum of the foot. At the same time, the main microrheological parameters (plasma viscosity, albumin, fibrinogen, red cell aggregation times, disaggregation threshold and red cell aggregate structure index) are measured in diabetic patients with good and poor glycemic control, with and without angiopathy. All the diabetics have a significant reduction of TcPO2 and have rheological disturbances. TcPO2 values are related significantly with plasma viscosity and with several parameters of aggregation-disaggregation phenomenon. As for microrheological parameter abnormalities, it seems that tissue hypoxia precedes clinical signs of angiopathy and depends on the metabolic state as rheological abnormalities. TcPO2 values are the result of numerous parameters as rheological parameters. It seems that TcPO2 measurement is able to provide useful informations about microcirculation in diabetes mellitus without clinical signs of tissue hypoxia.